Korekty księgowe w procesie kalkulacji ekonomicznej wartości dodanej - Hamrol, Mirosław; Burchardt, Robert (Adjusting Entries in EVA Calculation, 2005)
Recently there has been a rising interest and importance of the corporate value creation. In order to properly calculate value creation and make business decisions, it is necessary to redefine financial reporting. The result should be some amalgamation of financial, management and investment reporting known as value reporting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 152-167